Association between day-by-day and ambulatory blood pressure variability in type 2 diabetes patients. Issue 6 (December 2017) - Iuchi, Hiroyuki; Sakamoto, Masaya; Matsutani, Daisuke; Suzuki, Hirofumi; Kayama, Yosuke; Takeda, Norihiko; Utsunomiya, Kazunori
Abstract : It remains unclear whether ambulatory blood pressure variability (BPV) contributes toward day-by-day BPV, despite the fact that not only day-by-day but also ambulatory BPV is reported to be a risk factor for type 2 diabetes patients. This study aimed to determine the association between day-by-day BPV and ambulatory BPV, which is especially distinguished between diurnal and nocturnal BPV, in type 2 diabetes patients. Day-by-day and ambulatory BPV were assessed in 30 type 2 diabetes patients (aged 54±15 years; 87% men; glycated hemoglobin: 9.1±1.9%) in inpatient settings. Day-by-day systolic BPV was correlated significantly with diurnal systolic BPV ( r =0.426, P =0.019), but not nocturnal systolic BPV ( r =0.175, P =0.354). Multiple regression analysis showed that diurnal systolic BPV and diurnal mean systolic blood pressure were associated independently with day-by-day systolic BPV. With respect to type 2 diabetes, these findings suggest that day-by-day BPV is reflected in diurnal BPV rather than nocturnal BPV. Abstract : Supplemental Digital Content is available in the text.